Concise Guide to Databases - Lake, Peter; Crowther, Paul (Springer, 2013)
From tablets of stone through to libraries of parchments; from paper-based files to the electronic era, there is not one aspect of modern business that has avoided the need to collect, collate, organize and report upon data. The proliferation of databases and database technologies within modern times, has now been further secured by the use of the Internet to enable database integration on a massive scale. In amongst the innovation, the basic concepts remain. The need to organize— a topic that Codd reminded us could be best done by relational models—is now being challenged, as processor power and storage space become cheap and utilitylike with the advent of Cloud Computing infrastructure. But a glance at the past does much to inform future thinking, and this book serves to prepare the foundations of a mature approach to using database technologies in the 21st Century. In many cases, both established and emerging database technologies are readily available and free to use. As such they may appear free to implement, which fuels rapid adoption of technology that may not have been proven sufficiently, without the formal governance that other business norms might impose. This creates an exciting, risky, domain where commercial models can make or lose money depending upon how they embrace and realize the potential of the technology. Conversely, there is also an opportunity to solve problems when things go awry—and the accelerated innovation that we now witness, presents more opportunities and pitfalls, if we do not possess the requisite understanding of how databases should serve our needs. Proficiency in the field of databases is a combination of technical understanding, conceptual knowledge and business acumen. All of these traits are underpinned by education, and the need for professionals to continually update their knowledge. Since professionals not only face the challenge of when to introduce a technology, but also when not to adopt, it is important to understand the impact of failure as well as success. This book takes readers through the essential basics, before charting a path towards technical skill acquisition in the real-life context of business.
A Practical Introduction
Keywords: Database